2012
DOI: 10.1021/cn3001069
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizers of Neuronal and Mitochondrial Calcium Cycling as a Strategy for Developing a Medicine for Alzheimer's Disease

Abstract: For the last two decades, most efforts on new drug development to treat Alzheimer's disease have been focused to inhibit the synthesis of amyloid beta (Aβ), to prevent Aβ deposition, or to clear up Aβ plaques from the brain of Alzheimer's disease (AD) patients. Other pathogenic mechanisms such as the hyperphosphorylation of the microtubular tau protein (that forms neurofibrillary tangles) have also been addressed as, for instance, with inhibitors of the enzyme glycogen synthase-3 kinase beta (GSK3β). However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 118 publications
2
26
0
Order By: Relevance
“…An interesting connection between A β , calcium, and AD has been postulated by Arispe and coworkers [ 66 ], who suggested that A β oligomers can form calcium-permeable channels in membranes. It seems that energy deficits can promote this association, consistently with the observation that neurons with low cytosolic ATP levels showed a pronounced vulnerability to A β -induced toxicity [ 67 ]. In line with these reports, studies conducted in animal models (i.e., transgenic mice) highlighted an increase in calcium resting levels in the spines and dendrites of pyramidal cortical neurons [ 68 , 69 ], supporting the hypothesis that calcium-permeable channels can form in the neuronal plasma membrane close to the A β plaques, thanks to the high concentration of A β oligomers found in these areas [ 67 ].…”
Section: Calcium and Adsupporting
confidence: 65%
See 1 more Smart Citation
“…An interesting connection between A β , calcium, and AD has been postulated by Arispe and coworkers [ 66 ], who suggested that A β oligomers can form calcium-permeable channels in membranes. It seems that energy deficits can promote this association, consistently with the observation that neurons with low cytosolic ATP levels showed a pronounced vulnerability to A β -induced toxicity [ 67 ]. In line with these reports, studies conducted in animal models (i.e., transgenic mice) highlighted an increase in calcium resting levels in the spines and dendrites of pyramidal cortical neurons [ 68 , 69 ], supporting the hypothesis that calcium-permeable channels can form in the neuronal plasma membrane close to the A β plaques, thanks to the high concentration of A β oligomers found in these areas [ 67 ].…”
Section: Calcium and Adsupporting
confidence: 65%
“…It seems that energy deficits can promote this association, consistently with the observation that neurons with low cytosolic ATP levels showed a pronounced vulnerability to A β -induced toxicity [ 67 ]. In line with these reports, studies conducted in animal models (i.e., transgenic mice) highlighted an increase in calcium resting levels in the spines and dendrites of pyramidal cortical neurons [ 68 , 69 ], supporting the hypothesis that calcium-permeable channels can form in the neuronal plasma membrane close to the A β plaques, thanks to the high concentration of A β oligomers found in these areas [ 67 ]. Tau protein is also able to form ion channels in planar lipid bilayer, with lack of ion selectivity and multiple channels conductance, thus contributing to lower membrane potential, dysregulate calcium, depolarize mitochondria, or deplete energy stores [ 70 ].…”
Section: Calcium and Adsupporting
confidence: 65%
“…[22][23] There is preclinical and clinical evidence that the blockade of voltage-gated Ca 2+ channels (VGCC) may attenuate dementia, since an excessive and prolonged Ca 2+ entry into the cytosol leads to neurodegeneration and neuronal loss. [24][25][26] The VGCC blockade, both at presynaptic (P/Q-and Ntype VGCC) and at postsynaptic sites (L-type VGCC), has shown a neuroprotective effect in different animal models of neurodegeneration and excitotoxicity, such as the blockade of ω-agatoxin IVA in a rat ischemia model (P/Q-VGCC blocker), 27 the blockade by the synthetic version of ω-conotoxin MVIIA in a traumatic diffuse brain injury model in rats (N-type VGCC blocker), 28 that of verapamil in a focal ischemia model in rats (L-type VGCC blocker), 29 or those of nivaldipine and nitrendipine (L-type VGCC blockers) in an Aβ-induced toxicity model in mice. 30 Some VGCC antagonists have been tested in clinical trials for dementia and, according to the Cochrane report published in 2002, nimodipine can be of some efficacy for the treatment of AD.…”
Section: Introductionmentioning
confidence: 99%
“…43,57,74,108,109 Dantrolene, as an antagonist of RYRs on ER, mitigates AD pathology and may serve as a probe compound for future studies to treat Alzheimer's disease.…”
mentioning
confidence: 99%